Transações geradas pelo fluxo de recursos dos fundos e o efeito momento no Brasil - Gonzalez, Raphaela Mattos (2013)
The paper’s goal is test the instutional hypothesis for brazilian stocks momentum. We 'construct' a measure of demand shocks to individual stocks in the following steps: estimate the part of the mutual fund trading that is associated with capital flow; followed by the computation of the expected flow; and, finally, aggregate the expected flow induced trading across all mutual funds. As conclusion, we found that expected flow induced trading partially explains momentum in more liquid stocks.